The Influence of Organizational Culture and Non-Physical Work Environment on Organizational Commitment Among High School Teachers at Bina Muda Cicalengka - Riska Rahmawati; Khaerul Rizal Abdurahman (Green Publisher Indonesia, 2026)
Education is a key pillar of national development, determining the quality of human resources. Educational success is not only determined by the quality of individual teachers but also by their organizational commitment. Organizational culture and the non-physical work environment are thought to influence teacher commitment to their duties. This study aims to determine the influence of organizational culture and the non-physical work environment on organizational commitment among teachers at Bina Muda Cicalengka High School, both partially and simultaneously. This study used quantitative methods with data analysis in the form of multiple linear regression using SPSS version 27. Data collection was conducted by distributing questionnaires to 52 non-permanent teachers with more than five years of service. This study found that: 1) Organizational culture has a positive effect on organizational commitment among teachers at Bina Muda Cicalengka High School; 2) The non-physical work environment does not directly influence organizational commitment among teachers at Bina Muda Cicalengka High School; 3) Organizational culture and the non-physical work environment influence organizational commitment among teachers at Bina Muda Cicalengka High School. This means that the better the organizational culture and non-physical work environment, the higher the teachers' organizational commitment.